Effects of a Regular Endurance Training Program on Running Economy and Biomechanics in Runners - Rodriguez-Barbero, Sergio; González Ravé, José María; Juárez Santos-García, Daniel; Rodrigo-Carranza, Victor; Santos-Concejero, Jordan; González-Mohíno, Fernando (International Journal of Sports Medicine, 2023)
A regular endurance training program may elicit different adaptations compared to an isolated training method. In this study, we analyzed the effects of 8 weeks of a regular endurance training program on running economy (RE), particularly neuromuscular and biomechanical parameters, in runners of different athletic abilities. Twenty-four male runners were divided into two groups: well-trained (n=12) and recreational (n=12). Both groups completed a 4-min running bout at 13 and 17 km·h-1, respectively, for the recreational and well-trained group, and a 5-jump plyometric test pre-post intervention. During the training program, participants completed low-intensity continuous sessions, high-intensity interval training sessions, and auxiliary strength training sessions. RE, measured as oxygen cost and energy cost, decreased by 6.15% (p=0.006) and 5.11% (p=0.043), respectively, in the well-trained group. In the recreational group, energy cost of running, respiratory exchange ratio, and leg stiffness decreased by 5.08% (p=0.035), 7.61% (p=0.003), and 10.59% (p=0.017), respectively, while ground contact time increased by 3.34% (p=0.012). The maximum height of the 5-jump plyometric test decreased by 4.55% (p=0.018) in the recreational group. We suggest that 8 weeks of regular endurance training leads to an improvement of ~5% in RE in recreational and well-trained runners with different physiological adaptations between groups and few changes in biomechanical and neuromuscular parameters only in recreational runners.
Keywords: performance; running kinematics; athletes; training